The Analyzing of Sign in Exploring Jakarta Textbook, for Class 2, Elementary School. - Malik, Aulia Ananda; Salsabila, Salma; Sundari, Hanna (JEdu: Journal of English Education, 2023)
Textbooks are an important component in teaching and learning activities. At schools, language textbooks have roles to deliver the content materials and to facilitate students in producing and using the language, at the same time, textbooks can be a tool to present values and ideology through texts, dialogues, and images. The special characteristics of semiotic illustrations on the books, specifically a character of teacher in this case, can affect learners visual perceptions. Semiotic factors in the form of illustrations in a textbook can be analyzed or studied. The purpose of this current research is to analyze picture of sign provided by the teachers on the visual illustration in the textbook Exploring Jakarta, Elementary School, and used the visual illustration as the sample for the research through a visual semiotic analysis. To collect data (markers) and visual materials in the textbook, qualitative research method was employed. Based on Peirce's semiotic theory as data analysis of material (signified), then the representamen (signifier), object (referent), and interpretant are applied.